PHYLOGENETIC ANALYSIS OF TWO FISH GENUS: OSTEOCHILUS AND CYCLOCHEILICHTHYS - Nadia Syahirah, Radzali (Universiti Malaysia Sarawak(UNIMAS), 2015)
construct the phylogenetic tree of Osteochilus spp and Cyclocheilichthys spp using Cytochrome C Oxidase Subunit I (COI) gene and to study the genetic divergence of the Osteochilus spp and Cyclocheilichthys spp using COI gene. Samples were collected from Batang Kerang, Balai Ringin, Serian using three-layered gill net method. A total of three Cyclocheilichthys spp and one Osteochilus spp tissue samples were successfully processed for DNA analysis. The obtained sequences were aligned and edited using MEGA 6.06 program. construct the phylogenetic tree of Osteochilus spp and Cyclocheilichthys spp using Cytochrome C Oxidase Subunit I (COI) gene and to study the genetic divergence of the Osteochilus spp and Cyclocheilichthys spp using COI gene. Samples were collected from Batang Kerang, Balai Ringin, Serian using three-layered gill net method. A total of three Cyclocheilichthys spp and one Osteochilus spp tissue samples were successfully processed for DNA analysis. The obtained sequences were aligned and edited using MEGA 6.06 program. The genetic divergence was analysed using Kimura 2-parameter distances. Neighbor-Joining, Maximum- Likelihood and Maximum-Parsimony trees were constructed to determine the phylogenetic relationships between species. The genetic divergence between species ranged from 0 % (between C. apogon individuals) to 0.163% (between O. vittatus and C. armatus). The phylogenetic analysis suggested that Cyclocheilichthys spp and Osteochilus spp are of different genus. This study was able to determine the monophyletic of Cyclocheilichthys spp and Osteochilus spp based on the COI gene. The genetic divergence was analysed using Kimura 2-parameter distances. Neighbor-Joining, Maximum- Likelihood and Maximum-Parsimony trees were constructed to determine the phylogenetic relationships between species. The genetic divergence between species ranged from 0 % (between C. apogon individuals) to 0.163% (between O. vittatus and C. armatus). The phylogenetic analysis suggested that Cyclocheilichthys spp and Osteochilus spp are of different genus. This study was able to determine the monophyletic of Cyclocheilichthys spp and Osteochilus spp based on the COI gene.